Strategi Digital dan Inovasi Layanan untuk Meningkatkan Daya Saing UMKM Garuda Jaya - Wahyudi, Triyono Arief (ABDIMAS Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity aims to assist the Garuda Jaya MSME, a photocopying and printing business in Jakarta, in facing the challenges of increasingly fierce business competition. Based on observations and interviews, several key issues were identified, such as a lack of promotion through social media and the lack of additional services with marketable value. The proposal team used the Eisenhower Matrix, Effort-Impact Matrix, and SMART analysis to select and formulate appropriate solutions. The chosen solutions were the creation of an Instagram account for digital promotion and the addition of invitation and Yasin book design services. Implementation was carried out through training and mentoring, including the use of free resources from Freepik.com. The results of this activity showed increased business visibility and new customer interest in additional services, which are expected to enhance the competitiveness and sustainability of partner businesses.